Tegami Bachi, letter bee. Volume 20, Shine - Asada, Hiroyuki, 1968-; Amtower, Rich (Shonen Jump manga., 2017)
"What is the truth behind Amberground? As Lag and his friends descend to the center of their twilight world, they learn more than they ever dreamed possible. With civilization collapsing and the end of the world at hand, the time has come for Lag to lead the people of Amberground to hope and light at last" -- provided by publisher.